1997
DOI: 10.1016/s0042-6989(96)00118-6
|View full text |Cite
|
Sign up to set email alerts
|

Local photoreceptor alignment measured with a scanning laser ophthalmoscope

Abstract: The aim of this study was to develop a fast test for local photoreceptor alignment. Photoreceptor alignment is an important indicator of retinal integrity. Digitized images of fundus reflectance were obtained for 20-30 pupil entry positions with a custom built scanning laser ophthalmoscope (SLO). The data permitted the calculation of curve peakedness of the optical Stiles-Crawford effect (SCE) as a function of retinal location. We found that the peakedness is low in the central 0.5 deg, reaches a maximum at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 25 publications
4
58
0
Order By: Relevance
“…He confirmed this prediction psychophysically, and since then it has been well established that ρ varies with retinal eccentricity. 3,7,15 Enoch and Hope 7 measured ρ from 0 to 10 deg in the temporal retina. They found that ρ was minimum at the center of the fovea, increased rapidly out to 2-5 deg eccentricity, and then decreased very slowly.…”
Section: A Variation In Directional Tuning With Retinal Positionmentioning
confidence: 99%
See 3 more Smart Citations
“…He confirmed this prediction psychophysically, and since then it has been well established that ρ varies with retinal eccentricity. 3,7,15 Enoch and Hope 7 measured ρ from 0 to 10 deg in the temporal retina. They found that ρ was minimum at the center of the fovea, increased rapidly out to 2-5 deg eccentricity, and then decreased very slowly.…”
Section: A Variation In Directional Tuning With Retinal Positionmentioning
confidence: 99%
“…Starr et al, 31 using a 2-min test target and careful control of the optical correction of the eye, found that for the very center of the retina the cones' directional sensitivity was flat across the pupil. Recently Delint et al 15 used an optical method based on a scanning laser ophthalmoscope to measure ρ as a function of retinal position. In agreement with Enoch and Hope 7 and Gorrand and Delori, 13 de Lint et al 15 found that ρ was small in the center of the fovea and increased to either side.…”
Section: A Variation In Directional Tuning With Retinal Positionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different groups have used slightly different approaches. For example, Van Blockland 10 measured the scattering diagrams as the exit pupil was scanned along one axis; Gorrand and Delori 11 scanned both the entry pupil (for illumination) and the exit pupil (for light collection); Burns et al 6,9 imaged the entire distribution of the light returning from the retina through the pupil for any given pupil entry position; and Delint et al 12 analyzed digitized images of the fundus reflectance obtained with a scanning laser ophthalmoscope for different pupil entry locations.…”
Section: Introductionmentioning
confidence: 99%